The influence of acacias on below canopy grass communities - Roberts, Anthony (Department of Biological Sciences, 2017)
The inﬂuence of acacia species through their varying life stages (seedlings, juveniles, adults and dead trees) on sub-canopy grass communities was investigated at various sites in the Hluhluwe-Umfolozi Park (HUP). There were signiﬁcant differences between classes (at p < 0.05} to each other and to the open sites, but to differing extents at the different rainfall regions within the HUP. Signiﬁcant differences occurred between young acacias and the open sites more frequently at the drier sites than at the wetter sites. Young acacias do not inﬂuence below canopy grass communities in the high rainfall regions. ln the low rainfall sites, the young acacias act as refugia for 'bunch' grass species in the sea of 'lawn'. A switch back to lawns occur below the adult acacias dominated by the 'lawn' grass Dactyloctenium australe which occurs at differing proportions to the 'bunch' grass Panicum maximum below the canopy depending on the extent of animal disturbance, measured as density of droppings. Rainfall was responsible for separating communities out between the various sites in HUP. However, the impact of animals on the grass communities within each of the sites had more inﬂuence on the resulting grass communities in each of the classes. The response of a variety of grass species to light levels failed to explain the presence of particular species below adult acacias and others away from the inﬂuence of these acacias. Succession is occurring between grass communities as a result of establishment of acacias with the process being more evident in the dry areas of the HUP. The grass communities in the high rainfall areas revert back to early successional communities more rapidly once a tree dies than they do in the low rainfall areas. The inﬂuence of the adult acacias on the below canopy soils is greater and affects grass communities for a longer period of time in thc low rainfall areas than it is in the high rainfall areas even after the tree has died.